COMPARISON OF POSTOPERATIVE ATRIAL FIBRILLATION IN PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFT WITH AND WITHOUT LONG CPB TIME - Ajwad Farogh; Ahsan Arif; Noman Izhar; Saima Jabeen; Muhammad Ali; Syeda Rabia Bukhari (Journal of Ayub Medical College Abbottabad, 2024)
Background: Postoperative atrial fibrillation (POAF) is frequently observed after cardiac surgery, and duration of Bypass Time (CPB) is an independent risk factor for postoperative atrial fibrillation (POAF). The main objective of the current study was to compare new onset Postoperative Atrial Fibrillation (POAF) in patients undergoing coronary artery bypass graft with and without long CPB time. Methods: A prospective comparative study design was used and conducted at the Cardiac Surgery Department in Bahawalpur- Pakistan which is a tertiary care health centre for the period of April 2020 to February 2021, a total of 110 patients were enrolled after getting institutional approval and informed consent from patients. The ethical protocol was followed throughout the study period. Data was entered and analyzed using SPSS version 25.0 and p-value <0.05 taking the level of significant. Results: A total of 110 patients were enrolled for the research, the average age of patients was 48.56±3.11 (age range 30-70), and there were 38(34.55%) & 72(65.45%) male and female patients observed respectively. The atrial fibrillation developed in 3(5.45) patients in without a long CPB time group as compared with the long CPB time group as 8(14.54%) with a statistically significant p-value of 0.043, postoperative IABP support with insignificant p-value of 0.234. Conclusion: Postoperative atrial fibrillation in patients undergoing coronary artery bypass graft is significantly higher with long CPB time as compared with without long CPB time